2000
DOI: 10.1306/2dc40938-0e47-11d7-8643000102c1865d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Outcrop Data for Flow Simulation

Abstract: An architectural analysis documents variations in bedding geometry and rock properties within a tide-influenced deltaic sandstone exposed in the Cretaceous Frontier Formation of central Wyoming, USA. Digital maps of bedding, lithofacies, and diagenetic cements, as well as vertical logs of grain size, lithofacies, and permeability, describe rock properties that potentially influence fluid flow behavior. These records are used to construct simulation models that assess the relative importance of different types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(63 citation statements)
references
References 29 publications
1
62
0
Order By: Relevance
“…Shale commonly affects flow behavior significantly (Willis and White, 2000), altering vertical permeability (Begg and King, 1985), sweep efficiency and breakthrough time (Jackson and Muggeridge, 2000) and upscaled multiphase flow properties. In the subsurface, the spatial distribution of shale is difficult to infer because the spacing of wells (hundreds to thousands of meters) is typically greater than shale dimensions.…”
Section: Point Barmentioning
confidence: 99%
“…Shale commonly affects flow behavior significantly (Willis and White, 2000), altering vertical permeability (Begg and King, 1985), sweep efficiency and breakthrough time (Jackson and Muggeridge, 2000) and upscaled multiphase flow properties. In the subsurface, the spatial distribution of shale is difficult to infer because the spacing of wells (hundreds to thousands of meters) is typically greater than shale dimensions.…”
Section: Point Barmentioning
confidence: 99%
“…Often, sedimentary strata are divided into multiple layers designated as aquifers or aquitards. The assumption is made that geological facies define the spatial arrangement of hydraulic properties dominating groundwater flow and transport behaviour (Anderson, 1989;Fogg, 1986;Klingbeil et al, 1999;Bersezio et al, 1999;Willis and White, 2000). This assumption can be checked using hydraulic property measurements to define facies.…”
Section: What Is a Hydrogeological Conceptual Model?mentioning
confidence: 99%
“…An experimental design approach and analysis of variance is used, which allows the relative effects of different variables to be quantified while minimizing the number of simulation experiments (Box and Draper 1987;Willis and White, 2000). Two sets of simulation experiments were carried out using the (A-E) Distribution of facies-association belts at the top of parasequences 1.4, 1.5, 1.6, and 1.7 and in the overlying coastalplain interval (after Deveugle et al, 2011), with the area of the models described in this paper shown by dashed lines.…”
Section: Design Of Simulation Experimentsmentioning
confidence: 99%